MENTAL WORKLOAD, JOB STRESS, AND LEADERSHIP TRUST SHAPING EMPLOYEE CREATIVITY VIA PSYCHOLOGICAL DISTRESS - Muh Na’afi Utama; Muhammad Sholahuddin (Universitas Nusa Cendana, 2026)
This study investigates the influence of mental workload, work stress, and trust in leaders on employee creativity and innovation at XYZ University, both directly and through psychological distress as a mediating variable. The research adopts a quantitative explanatory approach and involves employees who have been actively working for at least one year in academic or managerial roles. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS.The findings reveal that work stress negatively affects employee creativity and innovation, while trust in leaders plays an important role in encouraging innovative behavior among employees. Meanwhile, mental workload and psychological distress do not show a direct influence on creativity and innovation, and psychological distress does not mediate the relationship between the studied variables. The results highlight the importance of leadership quality and effective stress management in fostering creativity and innovation within organizations. Future research is recommended to expand the research context to different organizations, include additional relevant variables, and apply longitudinal or mixed-method approaches to better understand the psychological dynamics of employees in the workplace. Keywords: Creativity; Innovation; Leadership; Psychological Distress; Work Stress